Organotypic Rat Testicular Organoids for the Study of Testicular Maturation and Toxicology - Sakib, Sadman; Lara, Nathalia de Lima e Martins; Huynh, Brandon Christopher; Dobrinski, Ina (Frontiers in Endocrinology, 2022)
An in vitro system to study testicular maturation in rats, an important model organism for reproductive toxicity, could serve as a platform for high-throughput drug and toxicity screening in a tissue specific context. In vitro maturation of somatic cells and spermatogonia in organ culture systems has been reported. However, this has been a challenge for organoids derived from dissociated testicular cells. Here, we report generation and maintenance of rat testicular organoids in microwell culture for 28 days. We find that rat organoids can be maintained in vitro only at lower than ambient O2 tension of 15% and organoids cultured at 34°C have higher somatic cell maturation and spermatogonial differentiation potential compared to cultures in 37°C. Upon exposure to known toxicants, phthalic acid mono-2-ethylhexyl ester and cadmium chloride, the organoids displayed loss of tight-junction protein Claudin 11 and altered transcription levels of somatic cell markers that are consistent with previous reports in animal models. Therefore, the microwell-derived rat testicular organoids described here can serve as a novel platform for the study of testicular cell maturation and reproductive toxicity in vitro.